INTEGRATING ISLAMIC ECONOMIC VALUES AND INFORMATION SYSTEMS IN SUSTAINABLE TOURISM: A CASE STUDY OF RESILIENCE IN BADUY, BANTEN - Novi Rukhviyanti; Asto Purwanto; Putri Adinda (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the integration of Islamic economic values and information systems in promoting sustainable tourism, focusing on the resilience of the Baduy community in Banten, Indonesia. Sustainable tourism has emerged as a critical global agenda, requiring ethical, cultural, and technological alignment to ensure long-term socio-economic and environmental benefits. Islamic economic principles, such as justice, balance, and prohibition of exploitation, offer a normative framework for ethical tourism development. Concurrently, information systems play a pivotal role in enhancing tourism management, data-driven decision-making, and cultural preservation. Through a comprehensive literature review of scholarly works published over the last decade, this study synthesizes insights from peer-reviewed journals, academic books, and institutional reports. The findings reveal that integrating Islamic values with advanced information systems can foster community resilience while maintaining cultural authenticity. The Baduy community exemplifies a unique case where traditional values intersect with modern technological approaches to sustain tourism without compromising indigenous identity. This integration also provides practical implications for policymakers, tourism practitioners, and local stakeholders in designing inclusive and sustainable tourism strategies. The study highlights the need for collaborative frameworks that bridge religious ethics and technological innovation in tourism. Ultimately, the research contributes to the theoretical discourse on value-based sustainable tourism while offering actionable recommendations for culturally sensitive destinations.